Loading

Solve the equation log2(x + 3) + log2(x - 3) = 4

log2(x + 3) + log2(x - 3) = 4log2 [(x + 3)(x - 3)] = 4x^2 - 9 = 16x^2 = 25x = 5

A pair of laptops with a tutor displayed on one and a student on the other. The student is raising his hand to answer the teacher's question.
Need help with Maths?

Have a Free Video Meeting with one of our friendly tutors.

A pair of laptops with a tutor displayed on one and a student on the other. The student is raising his hand to answer the teacher's question.
Need help with Maths?

Have a Free Video Meeting with one of our friendly tutors.

A pair of laptops with a tutor displayed on one and a student on the other. The student is raising his hand to answer the teacher's question.
Need help with Maths?

Have a Free Video Meeting with one of our friendly tutors.